"sail:lab" - development and use of an e-learning application in mathematics and sport sciences - Gasser, I.; Günzel, S.; Hebbel-Seeger, A. (International Journal of Computer Science in Sport, 2006)
sail:lab, as an interdisciplinary project of mathematicians and sport scientists, uses the physical description of sailing to develop an E-Learning component, which can be integrated in Blended Learning scenarios in both departments. By calculating the forces and moments due to wind and current which take effect at sail, hull, rudder, and fin, the movement of a jolly-boat is visualized. An instantaneous execution of computation and a graphical user interface, which accomplishes the association of sailing instruments, enable an intuitive use, especially for sailing experienced users. So, sail:Iab originates an amended theory - practise transfer, that is material to reflection and consideration for sport students. In the opposite this simulation process is an exemplary instance for practise — theory transfer in mathematics.